The interface between humans and other primates: The case of the Republic of Guinea-Bissau - Catarina Casanova; Susana Gonçalves Costa (Mètode Science Studies Journal: Annual Review)
With this paper we invite the reader to join us to a field trip to Guinea-Bissau through our eyes as primatologists and to explore the entanglements between humans and non-human primates. The first time we went to the field was in 2003. After staying with an NGO for a while, we set up a field station in a protected area that was home to chimpanzees (Madina Field Station). However, soon we realized that «protected areas», «high-quality forest», or «suitable habitat for chimpanzees» would not make any difference for research – and, most importantly, for this ape’s conservation – without taking into consideration the locals’ attitudes. Humanized landscapes most probably will become the rule in the future, so finding a way for a peaceful coexistence is urgent.